Some External Characterizations of SV-Rings and Hereditary Rings - A. Haily; H. Rahnaoui (International Journal of Mathematics and Mathematical Sciences)
We introduce a new class of rings which we call AI-rings. By applying this property to endomorphism rings, we give characterizations of semi-Artinian V-rings and hereditary rings.